Coexistence of Adenomyosis and Its Effect on Survival in Patients with Endometrial Cancer - Ozan Can Polat; Ali Ulvi Hakverdi (Women’s Health and Multidisciplinary Research, 2026)
Background and Aim: To investigate the impact of coexisting adenomyosis on clinicopathological characteristics and survival outcomes in patients who underwent surgery for endometrial cancer. Materials and Methods: This retrospective, single-center cohort study included 124 patients who underwent surgical treatment for endometrial cancer between January 2015 and May 2022. Patients were categorized according to the presence or absence of adenomyosis based on the final histopathological examination. Demographic characteristics, pathological findings, treatment modalities, recurrence, and survival outcomes were compared between the two groups. Results: Among the 124 patients, adenomyosis was identified in 31 (25.0%). Endometrioid carcinoma was the predominant histological subtype (91.3%). The coexistence of adenomyosis was significantly associated with the presence of leiomyoma (p=0.002), whereas no significant association was observed with tumor histology (p=0.766). The overall 3-year survival rate was 88.0%. The 3-year survival rates were 86.4% in patients with adenomyosis and 88.7% in those without adenomyosis, with no statistically significant difference between the groups (p=0.427). Similarly, mortality rates did not differ significantly between the groups (22.6% vs. 18.3%, p=0.600). Conclusion: Coexisting adenomyosis was detected in one-quarter of patients with endometrial cancer. Although adenomyosis was associated with concomitant leiomyoma, it was not associated with survival outcomes in patients with endometrial cancer.